Factors Influencing the Effectiveness of Web-Based Learning in Selected Iranian Public Universities - Fariborzi, Elham (2009)
The development of learning in the society has always been a topic of concern for most countries. In Iran, discussions for its improvement focus primarily on the role of Information Communication Technology (ICT) on the existing educational systems. Traditional education criteria are no longer sufficient and suitable to cope with the changes that have been brought by ICT. Web-based learning is one of the new changes in Iranian educational systems. Although the role of web-based learning in supporting ICT integration is comprehended as critical, to date there are lack of scientific studies about its effectiveness in Iranian public universities. This study is to understand this information gap through comprehensive sources of data on web-based computer courses in Iran. The specific objectives of this study were to identify the socio-demographic and academic profiles of students, their perceived effectiveness of web-based learning, its relationship with a number of independent variables, and to determine learning factors that may influence the effectiveness of web-based learning. The study was primarily quantitative in nature and employed descriptive correlational research designs to collect data on students who were taking web-based computer courses at Iranian public universities during the first semester of 2008/09 (N=1500). The web questionnaire was used to obtain the required data and the number of valid responses was 482. The results of this study indicated that the average age of the respondents was about 26 years. Half of the students preferred to communicate via e-mail and about 57% of them preferred to download their course contents from files with the .swf extension (Flash Player files). Further, 80% of them indicated that they participated in the web-based courses because they could learn at their own pace and it could fit into their busy schedules. Some 49% of these students had jobs. On average, they spent about four hours a week to study using computers. However, the instructors suggested that for a three-credit computer course, at least six hours must be spent on the computer a week. In addition, 55% of the students perceived that the web-based computer courses were moderately effective. Further analysis showed that the percentage of second year students or above (Level 2) who perceived the web-based computer courses to be effective was higher than the first or second year students doing Level 1.